A novel extraction of trichosanthin from Trichosanthes kirilowii roots using three-phase partitioning and its in vitro anticancer activity. (June 2014) - Mondal, Arijit
Abstract Context: Three-phase partitioning (TPP), a unique technique which has been explored for protein separation, was used for extraction of trichosanthin (TCS). Objective: TPP was used to optimize the TCS extraction and to determine its anticancer activity. Materials and methods: The process consists of the simultaneous addition of t-butanol and ammonium sulfate to the aqueous slurry of Trichosanthes kirilowii Maxim (Cucurbitaceae) root powder. The extraction of TCS was optimized with respect to the concentration of ammonium sulfate loading, the ratio of t-butanol to slurry, extraction time and pH. The anticancer activity was performed using 3-[4, 5-dimethylthiazol-2-yl]-2, 5 diphenyl tetrazolium bromide (MTT) assay in vitro. Results: The extraction time with this technique is lower in comparison to conventional solvent extraction. The optimized protocol resulted in maximum recovery of 98.68% (w/w) protein within 1 h. The in vitro cytotoxic activity of the TCS was evaluated against HepG2 and WRL 68 cancer cell line and results showed that TCS possesses quite highly significant anticancer activity having IC50 values of 10.38 and 15.45 μmol/l, respectively, comparable to standard drugs. Conclusion: This framework is utilized as a basis for optimization for protein separation using TPP technique which is economical and eco-friendly.